Associations of Perceived Birth-Order Status and Family Harmony with Academic Achievement among Students at SMAN 1 Luhak Nan Duo, West Pasaman, Indonesia - Dewi Sriani; Yarmis Syukur; Yeni Karneli; Zadrian Ardi (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
Academic achievement is no longer a foreign concept in the world of education. It is a crucial goal for students to achieve in school. Various factors related to academic achievement have a significant influence, both internal and external. Perceived birth-order status and family harmony are two particularly important factors; however, to date, no specific study has been conducted to examine the relationship between these two variables and student academic achievement. This study was conducted to examine the relationship between perceived birth-order status and family harmony and students’ academic achievement. The research method employed was a correlational design, with a sample of 90 students at SMAN 1 Luhak Nan Duo. The results of the study empirically demonstrate that perceived birth-order status and family harmony have a positive and significant relationship with student academic achievement, both partially and simultaneously. Partially, the perceived birth-order status has a strong relationship with students’ academic achievement, with a correlation coefficient of 0.626. Similarly, the variable of family harmony was found to have a strong relationship, with a correlation coefficient of 0.693. The results of the simultaneous analysis also indicate that the perceived birth-order status and family harmony have a strong relationship with academic achievement, with a correlation coefficient of 0.763. This proves that birth order and family harmony are closely related to students' academic achievement. However, the findings of this study cannot yet be generalized due to the relatively small sample size. Therefore, the researcher strongly recommends that other researchers conduct follow-up studies with a larger sample size, broader characteristics, a wider scope of research, and more comprehensive methods.